Interferon-Free Strategies without a Nucleoside/Nucleotide Analogue - Welzel, Tania Mara; Zeuzem, Stefan (Seminars in Liver Disease, 2014)
The identification of viral and host factors involved in hepatitis C virus (HCV) replication was a key prerequisite for the discovery and further exploration of antiviral drug targets. As of today, numerous direct-acting antiviral agents (DAAs), as well as host-targeting agents (HTAs), have been developed and entered clinical testing. The goal to omit pegylated interferon due to its unfavorable side-effect profile from novel HCV therapeutic approaches led to an expedited design and competitive conduct of DAA combination trials striving for easily applicable, all-oral HCV treatments. Approval of several interferon-free regimens is awaited in the near future (2014/2015). Results of different DAA combination trials (without nucleos(t)ide polymerase inhibitors) and trials involving HTAs are reviewed herein.
Keywords: interferon-free HCV treatment; direct-acting antiviral agents; NS3/4A protease inhibitors; NS5A inhibitors; non-nucleoside polymerase inhibitors; host-targeting agents